Gaya Kepemimpinan Di Pondok Pesantren Modern Putri Al-Mawaddah 2 Desa Jiwut Kec. Nglegok, Kab. Blitar - Khusumawati; Yasin Nurfalah (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
This research is framed by a large topic of leadership. More specifically this research is directed to analyze the tendency of leadership style in Islamic educational institutions. The subject is Putri Al Mawaddah Islamic Boarding School 2, Jiwut Village, Nglegok District, Blitar Regency, East Java. This study uses a descriptive qualitative approach. The focus of this research is about: 1) the tendency of leadership style, and 2) several aspects that contribute positively to the practice of leadership style. The research data was collected through interview, observation, documentation, and questionnaire techniques. While the analysis of the data follows the direction of Miles and Huberman which includes steps: 1) Data reduction, 2) Data display and 3) Conclusions. The results of this study concluded that: 1) The tendency of the leadership style at Putri Al Mawaddah Islamic Boarding School 2, Jiwut, Nglegok, Blitar Regency. the most dominant is democratic leadership; and 2) Some aspects that contribute to the practice of leadership style at the Putri Al Mawaddah Islamic Boarding School 2, Jiwut, Nglegok, Blitar Regency include: a) hereditary aspects; b) geographical; c) economy; d) aspects of the target vision and mission; and e) characteristics and advantages of boarding schools.